Is osteoarthritis one disease or a collection of many?. (15th December 2017) - Deveza, Leticia A; Loeser, Richard F
Abstract: OA is a multifaceted and heterogeneous syndrome that may be amenable to tailored treatment. There has been an increasing focus within the OA research community on the identification of meaningful OA phenotypes with potential implications for prognosis and treatment. Experimental and clinical data combined with sophisticated statistical approaches have been used to characterize and define phenotypes from the symptomatic and structural perspectives. An improved understanding of the existing phenotypes based on underlying disease mechanisms may shed light on the distinct entities that make up the disease. This narrative review provides an updated summary of the most recent advances in this field as well as limitations from previous approaches that can be addressed in future studies.